Early motor repertoire and neurodevelopment at 2 years in infants born extremely preterm or extremely‐low‐birthweight. (1st February 2022) - Kwong, Amanda K. L.; Doyle, Lex W.; Olsen, Joy E.; Eeles, Abbey L.; Lee, Katherine J.; Cheong, Jeanie L. Y.; Spittle, Alicia J.
Abstract: Aim: To determine the relationship between early motor repertoire and 2‐year neurodevelopment in infants born extremely preterm (<28 weeks' gestation) or extremely‐low‐birthweight (ELBW) (<1000g). Method: This was a geographical prospective cohort of 139 infants born extremely preterm/ELBW (mean gestational age 26.7 weeks, standard deviation [SD] 2.0, 68/139 [49%] male), with parent‐recorded videos suitable for scoring the General Movements Assessment (GMA). Motor repertoire was assessed using the Motor Optimality Score‐Revised (MOS‐R), with and without the fidgety movement subsection, and the GMA alone at 12 to 13 +6 weeks corrected age and 14 to 15 +6 weeks corrected age. At 2 years corrected age, impaired development was defined as Bayley Scales of Infant and Toddler Development, Third Edition motor and cognitive development scores 1SD or less relative to controls born at term; paediatricians diagnosed cerebral palsy (CP). Results: Greater MOS‐R scores at 14 to 15 +6 weeks corrected age were associated with lower odds of CP (odds ratio [OR] per 1‐point increase=0.83, 95% confidence interval [CI]=0.71–0.99), and motor (OR=0.93, 95% CI=0.87–0.99), or cognitive impairment (OR=0.94, 95% CI=0.88–0.99). Absent/abnormal GMA at 14 to 15 +6 weeks was associated with CP and motor delay. There was little evidence that MOS‐R scores at 12 to 13 +6 weeks were associated with neurodevelopmental outcomes at 2 years. Interpretation: Poorer MOS‐R scores and absent/abnormal GMA, scored from parent‐recorded videos at 14 to 15 +6 weeks gestational age, are associated with CP and developmental impairment in 2‐year‐old infants born extremely preterm/ELBW. Resumen: Objetivo: Determinar la relación entre el repertorio motor temprano y el neurodesarrollo a los 2 años en bebés nacidos extremadamente prematuros (<28 semanas de gestación) o con peso extremadamente bajo al nacer (ELBW) (<1000 g). Método: Esta fue una cohorte prospectiva geográfica de 139 bebés nacidos extremadamente prematuros/PNEB (edad gestacional media 26, 7 semanas, desviación estándar [DE] 2, 0, 68/139 [49 %] varones), con videos grabados por los padres adecuados para calificar los Movimientos Generales (GMA‐ siglas en ingles). El repertorio motor se evaluó utilizando la puntuación de optimización motora revisada (MOS‐R), con y sin la subsección de movimiento inquieto, y los GMA sola a las 12 a 13+6 semanas de edad corregida y a las 14 a 15+6 semanas de edad corregida. A los 2 años de edad corregida, el deterioro del desarrollo se definió como puntajes de desarrollo motor y cognitivo de Bayley Scales of Infant and Toddler Development, Third Edition, con 1 desviación estándar o menos en relación con los controles nacidos a término. La parálisis cerebral (PC) fue diagnosticada por los pediatras. Resultados: Mayores puntajes de MOS‐R a las 14 a 15+6 semanas de edad corregida se asociaron con menores probabilidades de PC (odds ratio [OR] por aumento de 1 punto = 0, 83, intervalo de confianza [IC] del 95 % = 0, 71–0, 99), y motor (OR=0, 93, IC 95 %=0, 87–0, 99), o deterioro cognitivo (OR=0, 94, IC 95 %=0, 88–0, 99). Los GMA ausente/anormal a las 14 a 15+6 semanas se asoció con PC y retraso motor. Hubo poca evidencia de que las puntuaciones MOS‐R a las 12 a 13+6 semanas estuvieran asociadas con los resultados del desarrollo neurológico a los 2 años. Interpretación: Los puntajes más bajos de MOS‐R y GMA ausente/anormal, calificados a partir de videos grabados por los padres a las 14 a 15+6 semanas de edad gestacional, están asociados con PC y deterioro del desarrollo en bebés de 2 años nacidos extremadamente prematuros/PNEB. Resumo: Objetivo: Determinar a relação entre o repertório motor precoce e o neurodesenvolvimento aos 2 anos em recém‐nascidos prematuros extremos (<28 semanas de gestação) ou de extremo baixo peso (EBP) (<1000g). Método: Este foi uma coorte prospectiva geográfica de 139 bebês nascidos prematuros extremos/EBP (idade gestacional média 26, 7 semanas, desvio padrão [DP] 2, 0, 68/139 [49%] do sexo masculino), com vídeos gravados pelos pais e adequados para pontuar a Avaliação de Movimentos Gerais (GMA, sigla em inglês). O repertório motor foi avaliado usando o Escore Motor Ótimo Revisado (MOS‐R, sigla em inglês), com e sem a subseção de movimento fidgety, e apenas o GMA em 12 a 13+6 semanas de idade corrigida e 14 a 15+6 semanas de idade corrigida. Aos 2 anos de idade corrigida, o desenvolvimento prejudicado foi definido pelas pontuações no desenvolvimento motor e cognitivo pela Bayley Scales of Infant and Toddler Development, Third Edition, com 1 desvio padrão ou menos em relação aos controles nascidos a termo; pediatras diagnosticaram a paralisia cerebral (PC). Resultados: Maiores pontuações no MOS‐R em 14 a 15 + 6 semanas de idade corrigida foram associadas a menores chances de PC (razão de risco [OR] por aumento de 1 ponto = 0, 83, intervalo de confiança de 95% [IC] = 0, 71‐0, 99), e motor (OR=0, 93, IC 95%=0, 87–0, 99), ou comprometimento cognitivo (OR=0, 94, IC 95%=0, 88–0, 99). GMA ausente/anormal em 14 a 15+6 semanas foi associado com PC e atraso motor. Havia pouca evidência de que os escores MOS‐R em 12 a 13+6 semanas estivessem associados a resultados de neurodesenvolvimento aos 2 anos. Interpretação: Escores MOS‐R mais baixos e GMA ausente/anormal, pontuados a partir de vídeos gravados pelos pais entre 14 e 15+6 semanas de idade gestacional, estão associados a PC e comprometimento do desenvolvimento em bebês aos 2 anos nascidos extremamente prematuros/EBP.